Peningkatan Kemampuan Spasial Kebencanaan Masyarakat Pesisir Melalui Kegiatan Pemetaan Partisipatif (Studi Kasus Petani Garam Di Cirebon, Jawa Barat) - Anang Widhi Nirwansyah (UM Purwokerto Press, 2022)
The coastal area is currently the epicenter of various disasters, both sporadic and routine, that has an impact on human activities. This study examines the implementation of participatory mapping to improve the spatial ability of coastal communities, especially salt farmers. The approach used is qualitative with the subject of salt farmers in Pangenan District, Cirebon. Data collection on participatory mapping was collected through interviews and Focus Group Discussions on 14 farmer groups. The results of this study explore previous tidal floods (rob) in 2016 and 2018, which caused economic losses for farmers. The two events also provide different risk perceptions; in 2016, farmers who occurred during the harvest season had a greater risk. Meanwhile, the 2018 incident is considered a lower risk because it occurred during the land preparation season.